2015
DOI: 10.1007/s13105-015-0387-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide modulates electrical activity of murine myocardium via cGMP-dependent mechanisms

Abstract: Carbon monoxide (CO) is critical in cell signaling, and inhalation of gaseous CO can impact cardiovascular physiology. We have investigated electrophysiological effects of CO and their potential cGMP-dependent mechanism in isolated preparations of murine myocardium. The standard microelectrode technique was used to record myocardial action potentials (APs). Exogenous CO (0.96 × 10(-4)-4.8 × 10(-4) M) decreased AP duration in atrial and ventricular tissue and accelerated pacemaking activity in sinoatrial node. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…These results clearly indicate a tonic inhibitory role of the HO-1/CO system on cardiac frequency in developing zebrafish. These findings are in contrast to the positive chronotropic effects reported in mammals (Abramochkin, 2013;Abramochkin et al, 2015). Based on the present study, the inhibitory effects of CO do not appear to persist under hypoxic conditions because there was no further increase in f H when HO-1-deficient larvae were exposed to hypoxia.…”
Section: Presence Of Ho-1 In the Hearts Of Fishcontrasting
confidence: 96%
See 2 more Smart Citations
“…These results clearly indicate a tonic inhibitory role of the HO-1/CO system on cardiac frequency in developing zebrafish. These findings are in contrast to the positive chronotropic effects reported in mammals (Abramochkin, 2013;Abramochkin et al, 2015). Based on the present study, the inhibitory effects of CO do not appear to persist under hypoxic conditions because there was no further increase in f H when HO-1-deficient larvae were exposed to hypoxia.…”
Section: Presence Of Ho-1 In the Hearts Of Fishcontrasting
confidence: 96%
“…Previous studies demonstrated that exogenous application of CO to mouse sinoatrial node preparations caused an accelerated sinus rhythm, demonstrating a direct effect of CO on f H (Abramochkin, 2013). A positive chronotropic effect of CO also was observed in the working myocardium of mouse, providing further evidence that CO is involved in controlling cardiac frequency (Abramochkin et al, 2015). The constitutively expressed form of HO, HO-2, also is present in interstitial cells of Cajal (ICC) which act as pacemaker cells in the gastrointestinal tracts of mammals (Farrugia and Szurszewski, 1999).…”
Section: Presence Of Ho-1 In the Hearts Of Fishmentioning
confidence: 78%
See 1 more Smart Citation
“…Meanwhile, a role for cGMP is suggested by the observation of high levels of soluble guanylyl cyclase and cGMP in the sinoatrial node [ 48 ]. Indeed, cGMP-mediated inhibition of PDE3 has been suggested to increase cAMP concentration and accelerate AP firing rate in mouse sinoatrial nodes [ 49 ]. cGMP-mediated inhibition of PDE3 has also been shown to modulate cAMP levels in subcellular compartments involved in βAR signaling in ventricular myocytes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…P2Y stimulation leads to increase in NO production, following stimulation of sGC and rise of intracellular cGMP content. cGMP stimulates phosphodiesterase 2, which is one of the prevalent phosphodiesterase isoforms in working myocardium of rabbit [ 43 ] and mouse [ 44 ], and therefore reduces intracellular cAMP content. Decrease of cAMP level leads to attenuation of I CaL and subsequent AP shortening (see [ 45 ] for review).…”
Section: Discussionmentioning
confidence: 99%